1996
DOI: 10.1002/(sici)1097-4644(19960401)61:1<9::aid-jcb2>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen induces TGF-β1 activity and apoptosis of human MCF-7 breast cancer cells in vitro

Abstract: We report here that the antiestrogen tamoxifen (TAM) induces cell death in human breast cancer cell line MCF-7. We assessed the type of cell death induced by TAM in this breast cancer cell line on the basis of morphological and biochemical characteristics. Dying cells showed morphological characteristics of apoptosis, such as chromatin condensation and nuclear disintegration. DNA isolated from these cells revealed a pattern of distinctive DNA bands on agarose gel. The DNA fragmentation in MCF-7 cells induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 23 publications
2
38
0
1
Order By: Relevance
“…TGF-␤ has also been shown to induce apoptosis in a variety of cancer cell lines including MCF-7 cells (65,66). Flow cytometric analysis demonstrated that PTGF-␤ does signal G 1 cell cycle arrest in MCF-7 cells, as evidenced by an increase in the G 1 /S ratio from 1.1 in untreated cells to 21.8 following AdPTGF-␤ treatment (Fig.…”
Section: Ptgf-␤ Overexpression Can Lead To the Induction Of P21mentioning
confidence: 87%
See 1 more Smart Citation
“…TGF-␤ has also been shown to induce apoptosis in a variety of cancer cell lines including MCF-7 cells (65,66). Flow cytometric analysis demonstrated that PTGF-␤ does signal G 1 cell cycle arrest in MCF-7 cells, as evidenced by an increase in the G 1 /S ratio from 1.1 in untreated cells to 21.8 following AdPTGF-␤ treatment (Fig.…”
Section: Ptgf-␤ Overexpression Can Lead To the Induction Of P21mentioning
confidence: 87%
“…In MCF-7 cells, increased TGF-␤ levels have been associated with the induction of apoptosis in response to several anticancer agents, including tamoxifen (65). Recent evidence suggests that TGF-␤-mediated apoptotic signaling involves up-regulation of connective tissue growth factor, leading to reduced levels of Bcl-2 protein expression (81).…”
Section: Ptgf-␤ Overexpression Can Lead To the Induction Of P21mentioning
confidence: 99%
“…The biochemical hallmark of apoptosis is internucleosomal DNA cleavage (38)(39)(40), and it can be detected by the TUNEL assay or by conventional gel electrophoresis (41). In this report, we have presented data to demonstrate that the hPRLR antagonist, hPRL-G129R, is able to induce apoptosis by DNA fragmentation in multiple human breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…TGF is an autocrine regulator of cell growth in MCF-7 cells, and its secretion is stimulated by TAM (Perry et al 1995, Chen et al 1996, Knabbe et al 2000. Regulation of TGF secretion by TAM+AT was studied using specific ELISAs to quantitate medium TGF content.…”
Section: Modulation Of Tgf By At/tammentioning
confidence: 99%
“…Both retinoids and anti-estrogens block cell cycle progression at G 0 G 1 , and both agents reduce the hyperphosphorylated form of the retinoblastoma protein (pRb), indicating an important convergence point for their action (Wilcken et al 1996). Both retinoids and anti-estrogens downregulate Bcl-2 gene and protein expression (Wang & Phang 1995, Zhang et al 1999 and stimulate apoptosis in breast cancer cells (Perry et al 1995, Chen et al 1996, Liu et al 1996, Toma et al 1997. These similarities raise the possibility that synergism involves shared anti-proliferative pathways.…”
Section: Introductionmentioning
confidence: 99%